Neonatal Tetanus Evaluation of Treatment and a Proposal for Classification of Severity - Tjandra Husada; T. H. Rampengan; Ign. Harjanto; I. D. Arif; Muzief Munir (Indonesian Pediatric Society, 1976)
An evaluation was made on 22 neonates with Tetanus Neonatorum (age 5 - 21 days), who were admitted to the Military Hospital, Teling, Manado, in 1973. Seventeen of our patients were babies born in their homes and were delivered by the